Distribution of florfenicol and norfloxacin in ice during water freezing process: Dual effects by fluorine substituents. (15th October 2022) - Sun, Heyang; Chen, Tianyi; Zhang, Liwen; Dong, Deming; Li, Yanchun; Guo, Zhiyong
Abstract: Distribution in ice is regarded as one of important transport modes for pollutants in seasonal freeze-up waters in cold regions. However, the distribution characteristics and mechanisms of fluorinated antibiotics as emerging contaminants during the water freezing process remain unclear. Here, florfenicol and norfloxacin were selected as model fluorinated antibiotics to investigate their ice-water distribution. Effects of antibiotic molecular structure on the distribution were explored through comparative studies with their non-fluorinated structural analogs. Results showed that phase changes during the ice growth process redistributed the antibiotics, with antibiotic concentrations in water 3.0–6.4 times higher than those in ice. The solute-rich boundary layer with a concentration gradient was presented at the ice-water interface and controlled by constitutional supercooling during the freezing process. The ice-water distribution coefficient ( K IW ) values of antibiotics increased by 34.8%–38.0% with a doubling of the cooling area. The solute distribution coefficient ( K bs ) values of antibiotics at −20 °C were 65.6%–70.3% higher than at −10 °C. The K IW and K bs values of all antibiotics were negatively correlated with their water solubilities. The fluorine substituents influenced the binding energies between antibiotics and ice, resulting in a 1.1-fold increase in the binding energy of norfloxacin on the ice surface relative to its structural analog pipemidic acid. The results provide a new insight into the transport behaviors of fluorinated pharmaceuticals in ice-water systems. Graphical abstract: Image 1 Highlights: Antibiotic concentrations in water were 3.0–6.4 times higher than those in ice. Solute-rich boundary layer occurred at ice-water interface in freezing process. Ice-water distribution was controlled by freezing rate and diffusion rate. Fluorosubstituents affected distribution by altering solubility and binding energy.